Relacionamento com o cliente: uma análise do uso da estratégia de CRM e suas implicações em uma empresa de locação de vídeos em Fortaleza - Correia, Marcos Vasconcelos (2008)
This dissertation is a study on the relationship with the customer, more specifically, in relation to the work of CRM (Customer Relationship Management) and its contribution to a company that provides services in the industry of renting videos. The study focuses on the relationship that the company has with its customers, using CRM as a tool for overcoming competitiveness. This strategy aims at increasing the profits and profitability through customer satisfaction and consequently the achievement of competitive advantage for business. The work is to start a review of the literature highlighting the business strategy, competitiveness, marketing and its origin, relationship marketing, you appear very comprehensive information on topics such as: endomarketing, database, CRM, satisfaction and loyalty. It was a qualitative research conducted exploratory in nature which was developed through the research strategy of (case study) in a business of leasing and venda of movies (DVD`s and VHS`s), as already reviewed, located in Fortaleza- CE , Met through semi-structured interviews with the members / owners, as well as a supervisor and the general responsible for information technology system. The main objective was to review the work with CRM and its contribution to the company. In summary, it was found that although the company does not know in depth the CRM, works with an informal program, performing actions that isolated and with it shall remain in the market, however, to differentiate itself in the market is even more crucial investment in this program, because the trend is increasingly businesses to invest in relationships with their customers.